2008
DOI: 10.21273/hortsci.43.3.677
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Shape Analysis of Vitis Using Digital Photography

Abstract: Quantifying fruit shape is challenging, particularly when measurements are made on segregating populations of plants. Objective manual measurements can be performed on small samples of fruit, but this method is difficult and very time-consuming when dealing with larger samples or when shapes are complex or shape variations are slight. Subjective rating scales can also be used, but their effectiveness is questionable when done by multiple raters resulting from varying descriptive standards among individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The literature reports several attempts, with the use of computer vision, to characterize morphological attributes of grapes (Wycislo et al, 2008; Miao et al, 2012), to evaluate different cluster and berry traits (Kicherer et al, 2013; Cubero et al, 2014; Diago et al, 2014; Roscher et al, 2014; Tello and Ibanez, 2014; Aquino et al, 2017) and to assess the number of grapevine flowers per inflorescence (Diago et al, 2014; Aquino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports several attempts, with the use of computer vision, to characterize morphological attributes of grapes (Wycislo et al, 2008; Miao et al, 2012), to evaluate different cluster and berry traits (Kicherer et al, 2013; Cubero et al, 2014; Diago et al, 2014; Roscher et al, 2014; Tello and Ibanez, 2014; Aquino et al, 2017) and to assess the number of grapevine flowers per inflorescence (Diago et al, 2014; Aquino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Herzog et al (2014) have shown some initial results on the application of image analysis for high-throughput phenotyping in vineyards. Wycislo et al (2008) used different ratios, such as the major/minor axis ratio, shape factor, and compactness shape value, to estimate the shape of table grapes. Wycislo et al (2008) used different ratios, such as the major/minor axis ratio, shape factor, and compactness shape value, to estimate the shape of table grapes.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made for the determination of bunch morphology using image analysis. Wycislo et al (2008) used different ratios, such as the major/minor axis ratio, shape factor, and compactness shape value, to estimate the shape of table grapes. Chen et al (2010) configured an automated inspection system for grading grape bunches on the basis of their colour, size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, Diago et al 14 Several studies have been conducted for cluster morphological determinations using image analysis. Wycislo et al 15 used different ratios to estimate the shape of tablegrapes such as the major/minor axis ratio, shape factor, and compactness shape value. Recently, a new method for cluster peduncle detection was developed using image analysis.…”
Section: Introductionmentioning
confidence: 99%